Strategy and Implementation of Islamic Personality Development through the Internalization of Religious Values at Madrasah Aliyah Dakka, Bangladesh - Mahmudulhassan; Abuzar, Muhammad; Yafi, Lukman; Afiyah, Ishmah; Amelia, Ishma (Solo Universal Journal of Islamic Education and Multiculturalism, 2024)
This study aims to analyze the strategy and implementation of Islamic personality development through the internalization of religiosity values in Madrasah Aliyah Dakka, Bangladesh. By examining the educational approaches used, this study explores the extent to which Islamic values are internalized into students' personalities and their impact on their daily behaviour. The research method used is qualitative descriptive with a case study approach. Data were collected through in-depth interviews with teachers, students, and parents, as well as participatory observation and analysis of curriculum documents. The results of the study show that the internalization of religiosity values in Madrasah Aliyah Dakka is carried out through various strategies, including teaching that focuses on a deep understanding of Islamic teachings, extracurricular activities that reinforce Islamic values, and a school environment that supports the application of these values. The students involved showed significant improvements in aspects of Islamic personality, such as discipline, honesty, and social responsibility. The novelty of this study lies in the emphasis on a holistic approach to the development of Islamic personality that not only focuses on cognitive but also emotional and social aspects. This research has made a significant contribution to the development of an effective and relevant Islamic education model in the modern context, especially in Bangladesh. The implications of this study suggest that a comprehensive and structured coaching strategy can produce individuals with strong Islamic personalities, which in turn can contribute to the development of a more harmonious and civilized society.